Proteomic analysis to identify candidate biomarkers associated with type 1 diabetes - do Nascimento de Oliveira V (Dove Medical Press, 2018)
Valzimeire do Nascimento de Oliveira,1,2 Abelardo Barbosa Moreira Lima-Neto,1 Maurício Fraga van Tilburg,2 Ana Cristina de Oliveira Monteiro-Moreira,3 Marina Duarte Pinto Lobo,3 Davide Rondina,4 Virgínia Oliveira Fernandes,5 Ana Paula Dias Rangel Montenegro,5 Renan Magalhães Montenegro Júnior,5 Maria Izabel Florindo Guedes1,2 1Collegiate Nutrition Science, Laboratory of Biotechnology and Molecular Biology, Ceará State University, Fortaleza, Ceará, Brazil; 2Collegiate Biotechnology, Northeast Network of Biotechnology, Laboratory of Biotechnology and Molecular Biology, Ceará State University, Fortaleza, Ceará, Brazil; 3Center of Experimental Biology, University of Fortaleza, Fortaleza, Ceará, Brazil; 4School of Veterinary Science, Ceará State of University, Fortaleza, Ceará, Brazil; 5Faculty of Medicine, Federal University of Ceará and University Hospitals, Fortaleza, Ceará, Brazil Purpose: Type 1 diabetes mellitus (DM1) is one of the most common chronic diseases observed during childhood. The incidence of DM1 is increasing worldwide, and there is currently no way to prevent or delay the onset or to cure the disease. Most diseases, including diabetes, stem from abnormalities in the functioning of proteins, and some studies have reported the expression of protein variation to be involved in the development of DM1. Thus, the aim of this study was to investigate the differential expression of serum proteins in patients with DM1. Materials and methods: Serum of patients with DM1 (n=30) and healthy controls (n=30) was collected. A proteomic approach was used with depletion of albumin and immunoglobulin G chromatography on serum samples followed by data-independent, label-free mass spectrometric analysis. Results: A total of eight serum proteins were identified as being differentially expressed and involved in the immune system, lipid metabolism, and pathways of coagulation. DM1 was associated with the upregulation of six proteins: alpha-2-macroglobulin, apolipoprotein A-II, β2 glycoprotein I, Ig alpha-2 chain C region, alpha-1-microglobulin, and prothrombin. A total of two proteins were downregulated, including pregnancy zone protein and complement C4. Conclusion: To the best of our knowledge, these findings show differential expression of proteins revealing new proteins that may be involved in the development and progression of diabetes. Keywords: proteome, mass spectrometry, precision medicine, diagnosis